2022
DOI: 10.1038/s41559-022-01768-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial infections can select against Pseudomonas aeruginosa mutators because of quorum-sensing trade-offs

Abstract: Bacteria with increased mutation rates (mutators) are common in chronic infections and are associated with poorer clinical outcomes; especially in the case of Pseudomonas aeruginosa infecting cystic fibrosis (CF) patients. There is however considerable between-patient variation in both P. aeruginosa mutator frequency and the composition of co-infecting pathogen communities, and we investigated whether community context might affect selection of mutators. Using an in vitro CF model community, we show that P. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…Mutations within pqsR were underrepresented in the presence of mucin and competition (Figure 3). These results support the recent findings of Luján et al, who demonstrated that pqsR-regulated QS system is retained in the presence of competing taxa and mucin, likely due to the fitness benefits of retaining the redox agent pyocyanin, an effective anti-competitor toxin 18 . Mutations in QS transcriptional regulators pqsR and vqsM are commonly observed during in vitro evolution of P. aeruginosa [17][18][19]38,48,49 , but mutations in these genes are rarely observed in chronic adapted strains isolated from CF sputum 5,50 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mutations within pqsR were underrepresented in the presence of mucin and competition (Figure 3). These results support the recent findings of Luján et al, who demonstrated that pqsR-regulated QS system is retained in the presence of competing taxa and mucin, likely due to the fitness benefits of retaining the redox agent pyocyanin, an effective anti-competitor toxin 18 . Mutations in QS transcriptional regulators pqsR and vqsM are commonly observed during in vitro evolution of P. aeruginosa [17][18][19]38,48,49 , but mutations in these genes are rarely observed in chronic adapted strains isolated from CF sputum 5,50 .…”
Section: Discussionsupporting
confidence: 91%
“…These results support the recent findings of Luján et al, who demonstrated that pqsR-regulated QS system is retained in the presence of competing taxa and mucin, likely due to the fitness benefits of retaining the redox agent pyocyanin, an effective anti-competitor toxin 18 . Mutations in QS transcriptional regulators pqsR and vqsM are commonly observed during in vitro evolution of P. aeruginosa [17][18][19]38,48,49 , but mutations in these genes are rarely observed in chronic adapted strains isolated from CF sputum 5,50 . Our results suggest that mutations within these QS transcriptional regulators are dependent upon the interaction between the community composition and the physical environment, whereby intense competition coupled with the presence of mucin provide strong selection for the retention of these QS transcriptional regulators.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the context of co-infecting pathogen communities, the augmented mutation rates (mutators) of P. aeruginosa bacteria infecting CF patients are found to be encouraged only in the absence of other species [ 42 ]. This illustrates the tremendous advantages that could be endorsed by polymicrobial infections in strategies aiming at P. aeruginosa eradication.…”
Section: Main Textmentioning
confidence: 99%
“…This could be an important shortcoming, as for sex to remain selectively advantageous it is necessary for selection to be strong and dynamic (Charlesworth, 1993; Burt, 2000), and interspecific competitors could greatly influence both these requirements (Otto and Nuismer, 2004; Kawecki et al ., 2012). However, while interspecific competition can create fluctuating conditions, it can also constrain evolution (Luján et al ., 2022). Experimental evolution approaches have hitherto relied on evolving recombining clones in isolation.…”
Section: Introductionmentioning
confidence: 99%